HNRNPH1 promotes autophagy to inhibit the development of lung adenocarcinoma via the HSP90AB1/MAP1LC3B axis - Rong Li; Fen Li; Qian Liu; Xu Wu; Xiaowu Tan (Respiratory Research)
Abstract Background Lung adenocarcinoma (LUAD) is a prevalent subtype of lung cancer (LC) whose progression is regulated by multiple genes. This study sought to find the impact and mechanism of HNRNPH1 on LUAD. Methods The expression and role of HSP90AB1, HNRNPH1, and autophagy-related protein MAP1LC3B in LUAD were detected. Additionally, bioinformatics analysis, silencing and overexpression techniques, and in vivo modeling were used to explore the regulatory mechanisms of these proteins in the progression of LUAD. Results HSP90AB1 showed high expression in LUAD and was linked to a worse prognosis. Overexpression of HSP90AB1 significantly promoted the malignant phenotype of LUAD cells and inhibited MAP1LC3B-mediated autophagy. However, overexpression of HNRNPH1 could reverse the malignant phenotype resulting from HSP90AB1 overexpression and promote MAP1LC3B-mediated autophagy by binding to HSP90AB1 mRNA and inhibiting its protein expression. Animal experiments also revealed that overexpression of HNRNPH1 could inhibit tumor progression by promoting cellular autophagy. Conclusions We verified the key role of HSP90AB1, HNRNPH1, and MAP1LC3B in LUAD, and revealed a possible regulatory mechanism, namely, HNRNPH1 could inhibit the development of LUAD by promoting autophagy through the HSP90AB1/MAP1LC3B axis. These findings may offer new insights for improving the treatment and prognosis of LUAD. Clinical trial number Not applicable.